Tranexamic acid as maintenance treatment for non‐histaminergic angioedema: analysis of efficacy and safety in 37 patients. (October 2014) - Wintenberger, C.; Boccon‐Gibod, I.; Launay, D.; Fain, O.; Kanny, G.; Jeandel, P. Y.; Martin, L.; Gompel, A.; Bouillet, L.
Summary Angioedema (AE) is a clinical syndrome characterized by localised swelling lasting several hours. The swelling is often recurring and can be lethal if it is located in the laryngeal region. Much progress has been made recently in the treatment of acute episodes, but no consensus has been reached on maintenance treatment. We have performed a national retrospective observational study to assess the use of tranexamic acid (TA) as maintenance treatment for non‐histaminergic AE [hereditary AE (HAE) or idiopathic non‐histaminergic AE]. Records for 64 cases were collected from 1 October 2012 to 31 August 2013; 37 of these were included (12 HAE with C1‐inhibitor deficiency, six with HAE with normal C1‐inhibitor and 19 idiopathic non‐histaminergic AE). When treated with TA over six months, the number of attacks was reduced by 75% in 17 patients, 10 patients showed a lower level of reduction and 10 had the same number of attacks. In no instances were symptoms increased. No thromboembolic events were observed, and the main side effects were digestive in nature. Thus, TA, which is well tolerated and inexpensive, appears to be an effective maintenance treatment for some patients with HAE or idiopathic non‐histaminergic AE.